Adoption factors of electronic health record systems. (August 2019) - Spatar, Daria; Kok, Orhun; Basoglu, Nuri; Daim, Tugrul
Abstract: The main goal of the study is to investigate the factors that affect adoption of EHR systems. The adoption has been looked at through four lenses: users' satisfaction, impact on quality of care, infusion and diffusion of the technology. The study incorporates the results of the most important studies in the field. The findings of the research allow decision-makers to select an EHR that better suits needs of the users, to choose a strategy to avoid users' resistance and lack of support. The study offers a comprehensive framework that can be used in different settings, i.e. small and large clinics, developing and developed countries, etc. Also it contributes to the state of knowledge, as it provides an extensive analysis of the factors, both system- and user-related, that affect user adoption and proves applicability of TAM in the healthcare settings. Highlights: Investigation of the factors that affect adoption of EHR systems. Users' satisfaction, impact on quality of care, infusion and diffusion of the technology. A comprehensive framework that can be used in different settings.